Domestic water supply in rural Greenland:sufficiency, affordability and accessibility - Maréchal , Judith Y. A.; Hendriksen, Kåre Anders Rand; Truelstrup Hansen , Lisbeth; Gundelund, Casper; Erland Jensen , Pernille (International Journal of Circumpolar Health, 2022)
Global efforts are still under way to ensure sustainable development goal 6 of providing enough clean water to sustain public health in many regions, and especially in the Arctic where the remoteness of communities and the harsh climate make water provision especially challenging. This study aimed to examine the sufficiency, accessibility, and affordability of water supplies in rural Greenland. The state of the water supply was investigated using quantitative data on infrastructure and demographics. Qualitative data on water-related practices and perceptions were collected through fieldwork and interviews in a selection of settlements. Generally, the supply of drinking water was found to be sufficient and affordable for most. However, access was severely constrained by the lack of piping to rural homes (20% were piped). The daily water consumption of residents from un-piped households was between 13 and 23 L/d/cap, i.e. within the basic access level according to WHO, which is in theory not sufficient to sustain public health. Several health risks could be caused by the low daily consumption in un-piped homes, and water saving practices induced by it – i.e. the use of shared handwashing basins, and household water storage, which could lead to degradation of water quality at the point-of-use.